The Function of Autophagy as a Regulator of Melanin Homeostasis - Ki Won Lee; Minju Kim; Si Hyeon Lee; Kwang Dong Kim (Cells, 2022)
Melanosomes are melanocyte-specific organelles that protect cells from ultraviolet (UV)-induced deoxyribonucleic acid damage through the production and accumulation of melanin and are transferred from melanocytes to keratinocytes. The relatively well-known process by which melanin is synthesized from melanocytes is known as melanogenesis. The relationship between melanogenesis and autophagy is attracting the attention of researchers because proteins associated with autophagy, such as WD repeat domain phosphoinositide-interacting protein 1, microtubule-associated protein 1 light chain 3, autophagy-related (ATG)7, ATG4, beclin-1, and UV-radiation resistance-associated gene, contribute to the melanogenesis signaling pathway. Additionally, there are reports that some compounds used as whitening cosmetics materials induce skin depigmentation through autophagy. Thus, the possibility that autophagy is involved in the removal of melanin has been suggested. To date, however, there is a lack of data on melanosome autophagy and its underlying mechanism. This review highlights the importance of autophagy in melanin homeostasis by providing an overview of melanogenesis, autophagy, the autophagy machinery involved in melanogenesis, and natural compounds that induce autophagy-mediated depigmentation.